How circular is the circular economy? Analysing the implementation of circular economy in organisations. (16th July 2020) - Barreiro‐Gen, Maria; Lozano, Rodrigo
Abstract: Circular economy (CE) has become one of the most recent ways to address environmental sustainability. CE activities focus exclusively on one of three levels (macro level, meso level and micro level). The majority of CE research has focused on the macro and meso levels, whereas research on the micro level has been limited. This paper focuses on the latter by analysing how organisations have implemented the four Rs (reduction, repairing, remanufacturing and recycling). A survey was sent to a database of 5, 299 contacts from different organisations, from whom 256 complete responses were obtained. The results show that organisations focus on reducing and recycling more than repairing and remanufacturing and in particular on internal CE efforts. Some organisations that engage with the 4Rs do not do it under the CE umbrella, whereas some that claim to apply CE have low levels of engagement with the 4Rs. The results indicate that organisations are using the 4Rs to contribute to CE, but not all of them are aware that they are applying CE principles. The paper highlights that organisations need to improve their 4Rs efforts to contribute more to CE by better linking its theory with practice. CE also has to be implemented outside the organisations, in a more holistic way, for example, through better collaboration with stakeholders on CE efforts and activities. This research stresses that the gap between CE theory and practice needs to be closed to make CE circular.